The fashion crossroad method: Political and epistemological practices - Costa, Carla; Casarin, Carolina; Júnior, João Dalla Rosa; de Olivera Santos, Heloísa Helena; Medrado, Mi (Sustainability Challenges in the Fashion Industry, 2023)

The new black vanguard: Photography between art and fashion - Sargent, Antwaun (Aperture Foundation, 2019)

Decolonial fashion ethnography: ‘Before yesterday’ method - Medrado, Mi (International Journal of Fashion Studies, 2023)

Decoloniality and fashion: RCDF 10th anniversary - Medrado, Mi (Decolonial Zine on Fashion, 2023)
The Decoloniality and Fashion e-zine celebrates the 10th anniversary of the Research Collective for Decoloniality and Fashion! Please complete this form to receive a FREE copy

Pausing for thought: Lost and found - Cheang, Sarah (International Journal of Fashion Studies, 2022)

Decolonizing fashion [studies] as process - Cheang, Sarah; Rabine, Leslie; Sandhu, Arti (International Journal of Fashion Studies, 2022)

Creating african fashion histories: Politics, museums, and sartorial practices - Creating African Fashion Histories (Conference); Akou, Heather Marie; McGregor, JoAnn; Stylianou, Nicola (Indiana University Press, 2022)
genre: Catalogue d’exposition

Conversations on decoloniality & fashion on ‘decolonial aestheSis and fashion’ - Research Collective for Decoloniality & Fashion (Youtube, 2022)

Defining defashion: A manifesto for degrowth - Niessen, Sandra (International Journal of Fashion Studies, 2022)

Jade Kuro: Ditching ‘the ideal’ narrative - Olowo-Ake, Oluwasola Kehinde (International Journal of Fashion Studies, 2022)

Mahila1 à la mode: The auntie-fit croqui - Sandhu, Arti (International Journal of Fashion Studies, 2022)

Border garments: Fashion, feminisms, and disobedience - Martinez, Loreto (The Fashion Studies Journal, 2021)

Decoloniality and fashion in Brazil : Zine - Medrado, Mi (Decolonial zine on Fashion, 2021)

Decolonizing the curriculum? Transformation, emotion, and positionality in teaching - Cheang, Sarah; Suterwalla, Shehnaz (Fashion Theory, 2020)

Curating fashion as decolonial practice: Ndwalane’s Mblaselo and a politics of remembering - de Greef, Erica (Fashion Theory, 2020)

Fashion and the phantasmagoria of modernity: An introduction to decolonial fashion discourse - Jansen, M. Angela (Fashion Theory, 2020)

Fashion, its sacrifice zone, and sustainability - Niessen, Sandra (Fashion Theory: The Journal of Dress, Body & Culture, 2020)

Decolonizing fashion: Defying the ‘white man’s gaze’ - Jansen, Angela (Research Collective for Decoloniality & Fashion, 2019)

Re-thinking luxury in the museum fashion exhibition - Lezama, Nigel (Luxury, 2019)

Fashion history: A global view - Welters, Linda; Lillethun, Abby (Bloomsbury Academic, 2018)

Ethnicity - Baxter, Denise Amy; Cheang, Sarah (A Cultural History of Dress and Fashion in Age of Empire, 2017)

Racial plagiarism and fashion - Pham, Minh-Ha T. (QED: A Journal in GLBTQ Worldmaking, 2017)

Introduction - Craik, Jennifer; Jansen, M. Angela (Modern fashion traditions: negotiating tradition and modernity through fashion, 2016)

Interpreting “civilization” through dress - Niessen, Sandra (Berg Encyclopedia of World Dress and Fashion : West Europe, 2010)

Clothing: A global history or, the imperialists' new clothes - Ross, Robert John (Polity, 2008)

Afterword: Reorienting fashion theory - Niessen, Sandra (Re-Orienting Fashion the Globalization of Asian Dress, 2003)